Diffusion of innovations in developing countries: blockchain case study - Sztokfisz, Barbara (Dyfuzja innowacji do krajów rozwijających się: studium przypadku technologii blockchain, 2019)
Distributed Ledger Technologies (DLTs) have become a topic that is being more and more discussed in political, economic and scientific discourses. , also within economic sciences. Their potential to redefine many processes in the economy is growing, and there is a consensus in the scientific community about their revolutionary character. Blockchain is one of the DLTs and one of the breakthrough technologies distinctive for the Fourth Industrial Revolution. The aim of the paper is to draw attention to the potential of blockchain technology for developing countries and how it can contribute to the improvement of quality of life and fighting poverty. Following Schwab’s thesis, “the extent to which society embraces technological innovation is a major determinant of progress”. Therefore, developing countries should not disregard the potential of blockchain technology that can solve a lot of current problems and provide access to previously unreachable services with a relatively low cost (both implementation and subsequent maintenance cost)
Ekonomia XXI Wieku = Economics of the 21st Century, 2019, Nr 1 (21), s. 60-74
Keywords: blockchain; distributed ledger technology; economic growth; developing countries; diffusion of innovation; technologia rozproszonego rejestru; kraje rozwijające się; wzrost gospodarczy; dyfuzja innowacji